Validation of a fuel particle dissolution model with samples from the Red Forest within the Chernobyl exclusion zone. (November 2020) - Kashparov, V.; Salbu, B.; Simonucci, C.; Levchuk, S.; Reinoso-Maset, E.; Lind, O.C.; Maloshtan, I.; Protsak, V.; Courbet, C.; Nguyen, H.
Abstract: The contamination in the near exclusion zone of the Chernobyl nuclear power plant (ChNPP) with 90 Sr, 238-240 Pu and 241 Am is associated with irradiated nuclear fuel particles. Fit for purpose models enabling long term prediction of mobility and bioavailability of particle-associated radionuclides are crucial for radiation protection of humans and the environment, as well as for planning of remediation measures and future land use. In the present work, a dynamic fuel particle dissolution model developed in 1999–2002 is described and validated using data based on sampling in 2015. The model is based on the characterization of the radionuclide source term of the waste in a shallow sub-surface radioactive waste storage, trench #22, in the Chernobyl Pilot Site (CPS) located in the Red Forest, 2.5 km west of the ChNPP, as well as the description of physical and chemical properties of the fuel particles and subsequent radionuclide leaching into the soil solution. Transformation rate constants of the fuel particle dissolution model related to topsoil, radioactive waste trench and submerged materials, and drained cooling pond sediments, should largely control the mobility and bioavailability of radionuclides (e.g., solubility in the soil, migration to groundwater and transfer to plants). The predicting power of the Chernobyl fuel particle dissolution model with respect to radionuclide leaching dynamics was validated using samples from the same experimental site, showing that predicted particle leaching and subsequent mobility and bioavailability were within 46 ± 3% of the observed data. Therefore, linking source- and release-scenario dependent characteristics of radioactive particles to their potential weathering can provide information that can be implemented in impact assessments models for existing contaminated areas as well as for future events. Highlights: Chemically extra-stable particles in Chernobyl radioactive fallout are U–Zr particles. The proposed dissolution model predicted well radionuclide leaching from Chernobyl fuel particles. Mobile 90 Sr activity in the Red Forest waste burial site has reached maximum values. 90 Sr migration from trench burials to groundwater and vegetation is expected to decrease.